Elemen Dan Karakter Worldview Islam - Ahmad Aly Syukron Al Mubarok (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
This study explains that human elements and characters are cognitive components of socio-psychological factors. that something is true or false on the basis of evidence, suggestion of authority, experience, and intuition is very important called belief. Islam introduces that humans from ancient times to the last generation each know themselves and believe with their body and soul that the One God is Allah SWT. Thus, each of them must make Islam a way of life as interpreted by Islamic scholars who say and promote it as a complete and comprehensive way of life. Islam teaches its people to be simple in matters of life and not to transgress and drown in luxuries that may lead to destruction. Every belief, nation, culture or civilization and even everyone has their own worldview. The essence of the difference lies in the dominant factors in their respective views of life which may come from culture, philosophy, religion, belief, social values, or others.